2014
DOI: 10.1111/cei.12392
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer is associated with decreased expression of perforin, granzyme B and interferon (IFN)-γ by infiltrating lung tissue T cells, natural killer (NK) T-like and NK cells

Abstract: SummaryThere is a limited understanding how of lung cancer cells evade cytotoxic attack. Previously, we have shown reduced production of the cytotoxic mediator granzyme B by CD8 + T cells in lung cancer tissue. We hypothesized that lung cancer would be further associated with decreased production of granzyme B, perforin and proinflammatory cytokines by other cytotoxic lymphocytes, natural killer (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 16 publications
3
68
0
4
Order By: Relevance
“…Also, we found that the number of cells expressing granzyme B was significantly lower than the cells expressing CD8. Interestingly, it has been reported that a decreased proportion of granzyme B + cells in lung tumors was a result of soluble mediators, not identified yet, secreted probably by cancer cells (36). …”
Section: Discussionmentioning
confidence: 99%
“…Also, we found that the number of cells expressing granzyme B was significantly lower than the cells expressing CD8. Interestingly, it has been reported that a decreased proportion of granzyme B + cells in lung tumors was a result of soluble mediators, not identified yet, secreted probably by cancer cells (36). …”
Section: Discussionmentioning
confidence: 99%
“…Intratumoral NK cells exhibited defects in deegranulation and IFN-γ production. Another study noted release of soluble factors by NSCLC cells that inhibited granzyme B, perforin and IFNγ expression in intratumoral NK cells [120]. These data suggest local impairment of NK cells by the NSCLC tumor microenvironment.…”
Section: Natural Killer Cellsmentioning
confidence: 89%
“…Many reports have indicated that the dysfunction of NK cell and NKT cell is closely related to the occurrence and development of lung cancer (Hasegawa et al, 2014;Hodge et al, 2014), but the underlying molecular mechanisms involved in this process remain poorly understood. Tim-3, was originally identified for Th1-specific markers.…”
Section: Discussionmentioning
confidence: 99%